The multifaceted role of autophagy in cancer and the microenvironment. Issue 2 (9th October 2018) - Folkerts, Hendrik; Hilgendorf, Susan; Vellenga, Edo; Bremer, Edwin; Wiersma, Valerie R.
Abstract: Autophagy is a crucial recycling process that is increasingly being recognized as an important factor in cancer initiation, cancer (stem) cell maintenance as well as the development of resistance to cancer therapy in both solid and hematological malignancies. Furthermore, it is being recognized that autophagy also plays a crucial and sometimes opposing role in the complex cancer microenvironment. For instance, autophagy in stromal cells such as fibroblasts contributes to tumorigenesis by generating and supplying nutrients to cancerous cells. Reversely, autophagy in immune cells appears to contribute to tumor‐localized immune responses and among others regulates antigen presentation to and by immune cells. Autophagy also directly regulates T and natural killer cell activity and is required for mounting T‐cell memory responses. Thus, within the tumor microenvironment autophagy has a multifaceted role that, depending on the context, may help drive tumorigenesis or may help to support anticancer immune responses. This multifaceted role should be taken into account when designing autophagy‐based cancer therapeutics. In this review, we provide an overview of the diverse facets of autophagy in cancer cells and nonmalignant cells in the cancer microenvironment. Second, we will attempt to integrate and provide a unified view of how these various aspects can be therapeutically exploited for cancer therapy. Abstract : This review describes the impact of autophagy on the cancer cell as well as its micro‐environment including stroma, immune cells and endothelium. This is an unique and complete overview of the whole spectrum which was currently missing in literature. In addition, we discuss possible therapeutic strategies to modulate autophagy in cancer therapy.